“Sustitución parcial de harina de trigo (triticum sativum L.) por harina de pan de árbol (Artocarpus altilis F.) en la elaboración de pan de labranza y su evaluación físico químico” - Acuña Garcia, Elera (2005)
With the present investigation work it is looked for to substitute the whent flour partialy for flour of tree broad, in the elaboration of farm bread,since this way it would be impelling to the production and use of rich products in contained proteico that not yet have reached the industrial level, since it is distributed by the whole region San martin. For that which did work with the variety of (Artocarpus a/ti/is F.), the varety that has been able to expand until the moment and spread with more easiness. The study understood diverse rehearsals, so much of the matter prevalis as of the product, as well as phyisical chemical and sensorial analysis necessary. The samples of tree bread (Artocarpus a/ti/is F.) they were gathered in the town of Shapaja, located to 23 kilometers of District appoximately Tarapoto with a minimun temperature of 17ºC and a maxim of 35ºC located at 06° 1 i 15" longitu de west, to a height of 207 msnm. The seeds of tree bread present a from irregular longitudinal smoothed semi, with a weight average of 6,45g. And with a diametor average of 3,47cm. The next chemical analysis of the bread of rawtree was: Humidity 60,02% Protein 3,92% fat 3,57%, ash 1,69%, fibre 2,22%, carbohydrates 28,58%, with a density of 0,52 gr. I cm3 ., pH of 6,51 andan Acidity of 0,24% expressed as sulfuric acid. For the bread of tree pre- cooked it was: Humidity 65,01% Protein 2,53% fat 4,36%, ash 1, 16%, fibre 2,38%, carbohydrates 24,86%, with a density of 0,53 gr. I cm3 ., pH of 6,31 and an Acidity of 0,24% expressed as sulfuric acid. Once recepcionado the matter prevalis it preceded to a laundry, with drinkable water for the alimination of saludges. Subsequently it proceded to the selection of two samples for the drying, araw sample and one pre-cooked. The temperature to which was carried out the drying was for a while of 60ºC of 12 hours, proceding then to the mill in a mill of hammers. Subsequently it proceded to sift the samples for uniformizar the particles and the product was packed in bags of polyethylene of high density to avoid possible deteriorations of the product. Later on the composition chemist proximal both were determinad types of raw and pre-cooked flour. For flour of bread of raw tree gave the following ones as result: Humidity 10,55%, Protein 7,39% fat 6,23%, ash 2,02%, fibre 2,55%, carbohydrates 71,26%, pH of 5,99 and an Acidity of O, 13% expressed as Sulfuric acid for flour of bread of pre-cooked tree lt was of: Humidity 10,77%, Protein 8,08% fat 6,19%, ash 2,08%, fibre 1,84%, carbohydrates 71,04%, pH of 6,01 andan Acidity of O, 11% expressed as Sulfuric acid. The composition chemist proximal of the two types of samples was determined for a substitution of fluor of trigo/ harina of bread of raw tree, and level of substitution of 80/20, even obtained the following result. Humidity 25,33%, Protein 9,40%, fat 5,34%, fibre 1,32%, ash 2, 11%, carbohydrates 55,31 %, pH of 6,21 andan Acidity of 0,34% expressed as Sulfuric acid. And for a substitution of fluor of trigo/ harina of bread of pre- cooked tree and level of substitution of 80/20, was even the following: Humidity 25,64%, Protein 10, 14%, fat 6,57%, fibre 1,48%, ash 1,31%, carbohydrates 53,79%, pH of 6,02 and an Acidity of 0,32% expressed as Sulfuric acid. They were carried out analysis chemícal proximal and organoléptico of the final product, to the two tacts of samples of breads. For the sensorial analysis the method atectivo of the scale hedónica of five points was used, and for the analyses of this test Desing of was used titally at random (OSCA). With a level of significancia of 0,05 and the significant treatments of the carried out ANVA, was carried out by means of the test of stockings from Tukey to the level of 0,05. The breads with subtitution of 20% of flour of bread of raw tree, and the breads with substitution of 20% of flour of bread of pre-cooked tree, had bigger acceptance for the judges consumers for their characteristics physical chemical, as well as better color attributes, scent, flavor and texture, recommending substitute until to level of flour of tree bread for the atributes mentioned.